Assessment of the soil - geobotanical condition of forest fund land plots on the example of the Orlinogorsk forestry (Journal of Geography and Environmental Management, 2023)
Abstract: The land fund is in constant motion. Lands are transferred from some categories and lands to others. The deterioration of the ecological state of the lands, the development of erosion processes, desertification, salinization, pollution with chemical and radioactive substances, overgrowth of forest and shrub lands annually exclude significant areas from use.During the reconnaissance route-loop survey of land plots, types of plant associations were identified. Mainly, the identification of types of plant associations made it possible to conduct a preliminary assessment on the ground about the quality of the studied sites for the restoration of forests. Work has been carried out on the study of forest areas located on the territory of Northern Kazakhstan. The surveyed sites are located in the forest-steppe zone on the right-bank side of the Ishim River in the North Kokchetav subdistrict. The study of the soil was carried out by the method of laying soil sections and semi-sections with a description of the power of horizons. The soil structure was determined by the method of splitting soil samples. Based on the results of the study, recommendations were developed for the categories of areas. The areas of plots suitable for all major forest species and areas with existing forests, forest crops overgrown with self-seeding were also determined.General recommendations were formed during the direct conduct of surveys on the ground, but systematic monitoring, using remote sensing methods of the Earth, could facilitate the ongoing research. The development of the method of integrated ecological and geographical research in the future can significantly increase the efficiency of forest management work in general and minimize losses associated with environmental influences.
Keywords: soils, plant associations, soil logging, chemical analysis, forestry